Jawapan

2016-02-12T11:55:33+08:00
F(x) = px² + qx - 5

f(-1) = 1  →  p(-1)² + q(-1) - 5 = 1
                     p - q = 1 + 5
                     p - q = 6
f(1) = -9  →  p(1)² + q(1) - 5 = -9
                     p + q = -9 + 5
                     p + q = -4

p - q  = 6
p + q = -4 +
2p    = 2
     p = 2/2
     p = 1
p + q = -4
1 + q = -4
      q = -4 - 1
      q = -5

f(x) = x² - 5x - 5

f(x) = 1
1 = x² - 5x - 5
x² - 5x - 5 - 1 = 0
x² - 5x - 6 = 0
(x - 6) (x + 1) = 0
x - 6 = 0
     x = 6
atau
x + 1 = 0
     x = -1